Effect of Number leaves, Benzyl adenine Spraying on Characteristics of Date of Palm Phoenix dactylifera L. Fruits c.v Khidrawi and Mekkawy - Al-Shammari, Ghaleb Nasser; Mohammed, Abdulhadi Hussain (Journal of agricultural, environmental and veterinary sciences, 2019)
The study was carried out in one of the palm groves in the city of Baquba - Diyala province for the season 2016 on date palm varieties Khadrawi and Makkawi, In order to know the effect of the number of weakness by 8 and 10 (leaf.banuch-1) During operation pollination And sprayed by BA on bunch With concentrations 0, 50 and 100 mg.L-1 ,The spraying was done twice the first spray after three weeks of pollination and the second spray at the beginning of the Al-Khallal stage and their characteristics interactions in the physical, chemical, physiological and production. The results of the study showed that the treatment of leaves pruning 10 lafe. banuch-1 was significant increase on Fruit weight, size, water content, TSS, reduced sugar content, increased fruit ripeness. Spraying with BA has a concentration of 100 mg. L-1 to significant differences on Fruit weight, size, water content, TSS, increased fruit ripeness. The results of the study showed that the Makkawi class was significant increase on Fruit weight, size, water content, TSS, increased fruit ripeness. The overlap between leaves pruning (10 leaf. baunch-1) and sprayed with BA (100 mg. L-1), significant increase on Fruit weight, size, water content, TSS, increased fruit ripeness. The overlap between leaves pruning (10 leaf. baunch-1) and Makkawi class, significant increase on Fruit weight, size, water content, TSS, increased fruit ripeness. The overlap between Spraying with BA (100 mg. L-1) and Makkawi class, significant increase on Fruit weight, size, water content, TSS, increased fruit ripeness.